2010
DOI: 10.1017/s1041610210000104
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders in the elderly

Abstract: Eating disorders do occur in the elderly and should be included in the differential diagnosis of unexplained weight loss in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
70
2
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 39 publications
2
70
2
6
Order By: Relevance
“…1,12,13 A review of the literature on eating disorders in older people showed the mean age of patients to be 68.6 years, 88% of whom are women, and 81% of all cases of eating disorders were diagnosed as anorexia nervosa. 9 It is also noteworthy that 69% of cases of anorexia nervosa in this population were late onset, as opposed to the more common early onset. Our case seemed to be more consistent with late-onset anorexia nervosa.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…1,12,13 A review of the literature on eating disorders in older people showed the mean age of patients to be 68.6 years, 88% of whom are women, and 81% of all cases of eating disorders were diagnosed as anorexia nervosa. 9 It is also noteworthy that 69% of cases of anorexia nervosa in this population were late onset, as opposed to the more common early onset. Our case seemed to be more consistent with late-onset anorexia nervosa.…”
Section: Discussionmentioning
confidence: 70%
“…Despite case reports and literature reviews of late-onset eating disorders, a controversy exists as to whether eating disorders can initially manifest later in life or are a recurrence of an early-onset eating disorder. 1,9,12,13 Patient records were reviewed for individuals aged Ͼ50 years who were admitted to national eating disorders center over a period of 10 years in an attempt to clarify this issue of eating disorders that present late, but the review found no cases of late-onset eating disorders in that population. 3 The possibility that eating disorders in older persons are neither well recognized nor diagnosed, or that older persons are more adept at disguising their eating disorder, should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations